Strategies and resources for nurse leaders to use to lead with empathy and prudence so they understand and address sources of anxiety among nurses practising in the era of COVID‐19. Issue 1 (15th October 2020) - Hofmeyer, Anne; Taylor, Ruth
Abstract: Aims: Identify strategies and resources for nurse leaders to use to lead with empathy and prudence to improve quality of care and to ease the psychological toll on nurses caring for patients with COVID‐19. Background: In a 2020 report, clinicians caring for patients during the COVID‐19 pandemic said their healthcare leaders needed to: 'hear me, protect me, prepare me, support me, and care for me'. These words provide an action plan for nurse leaders to communicate, educate and support nurses to practice competently and safely (physically and mentally) in the context of COVID‐19. Design: Discursive paper. Method: Identification and inclusion of relevant international evidence with clinical discussion. Findings: Nurse leaders can mobilise system and individual level strategies and resources to support nurses to manage pandemic‐related issues including: anxiety due to the risk of infection, supporting anxious children, mitigating moral injury; providing safe and quality nursing care for patients with COVID‐19 and end‐of‐life care as needed; supporting relatives who cannot be present with a dying relative and care for grieving relatives and colleagues. We categorise a selection of evidence‐based, online sources providing current COVID‐19 information, practice updates and resources to develop personalised self‐care plans to ease anxiety and support renewal and resilience. Conclusions: Nurse leaders must ensure adequate PPE supply, upskill nurses to provide safe, quality care for patients with COVID‐19 and promote restorative self‐care plans. Relevance to clinical practice: The strategic actions nurse leaders take today can positively impact nurses' well‐being and ability to provide safe and quality care for patients in the context of COVID‐19.